Angiogenesis in villous chorangiosis observed by ultrastructural studies - Soma, Hiroaki; Murai, Noriko; Tanaka, Kayoko; Oguro, Tatsuo; Kokuba, Hiroko; Fujita, Koji; Mineo, Shoichiro (Medical molecular morphology, 2013)
Chorangiosis is microscopically designated as more than ten terminal capillaries within the villous stroma of the placenta and is mostly related to chronic fetal hypoxia. However, the histogenetic relationship between increased number of terminal villous capillaries and chronic hypoxia has not yet been clarified. Of 665 placentas histologically examined at Saitama Medical University from 2003 to 2010, chorangiosis was found in 58 cases (8.7 %), which were mostly more than 35 gestational weeks. In addition, low birth weight (less than 2,500 g) infants (74.1 %) and those who suffered from cardiac anomalies, chromosome anomalies, and single umbilical artery comprised 32.7 % of cases. Placental lesions were associated with chorangiosis involved in infarct (46.6 %), intervillous thrombosis (20.7 %), and marginal hemorrhages (22.4 %). Scanning electron microscopic studies showed narrowing of vessel ostium and disorders of endothelium in the umbilical cord vessel complicated by chorangiosis. Furthermore, in transmission electron microscopic observation, not only the chorionic villi had multiple enlarged vessels within the villous stroma, but we also found that new capillaries were formed by angiogenesis with endothelial cells derived from fibroblasts under the chronic hypoxic state.